Risk Factors of Acute Kidney Injury Following Orthotopic Liver Transplantation - Yuan, Yu-Jing; Wan, Lei; Xue, Zhao-Jing; Xue, Fu-Shan (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Yuan YJ, Wan L, Xue ZJ, Xue FS. Risk factors of acute kidney injury following orthotopic liver transplantation. Turk J Gastroenterol. 2022;33(9):808-810.